Evaluating the science teacher according to the (NCATE) standard from the point of view of educational supervisors - Hanan Kazem Abd ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
The current research aims to evaluate the science teacher a according to the From the viewpoint of educational supervisors in (NCATE) criterion Misan Governorate, this study has confirmed criterion (NCATE) and mean the national Accreditation council for teacher predation programs and consists of a set of key criterion that serve the science teacher and help him in the correct evaluation during the profession as a science teacher is the guide and guide for the educational process the research has prepared a list of the main areas of the number (8) areas from which (51) subparagraphs emerge from each of the field in their initial from prepared in the form of an open questionnaire annex(1) after reviewing the Arab and in ternational studies and projects, the criterion (NCATE) in clouded the following fields (the profession of the science teacher - the personal and moral character - the educational alternatives to punishment- the educational programs- the curriculum –the teaching staff- the methods of teaching science and the educational means- the field experiences and the scientific activities) as part of the profession of the science teacher, the researcher used the statistical method, including the weighted media and the percentage weights, and through that the following results were reached : 1-The science teacher Evaluation according to a criterion (NCATE) was not at the required level compared to the assumed spoken percentage adopted by the researcher ,which (75%) according to the opinions of experts, as(33) paragraphs out of (51) paragraphs mentioned in the standard prepared for the study and its percentage (64,70%) . 2-The field of (professional competence) was ranked first and by weigh percentage (78%) while the field of (personal and moral character), was ranked second and by percentage (78%) , and the field (methods of teacher sciences and educational means )at third rank, with a percentage of (77,66%) followed by the field of (curriculum) at the fourth ran with percentage (71%) while the field of (educational al ternaries for punishment) at the fifth rank with arate of (69,66%) while the( field experiences and scientific activities) at the sixth rank and wither a percentage (69%) while the field (the teaching staff) at the seventh rank, with a percentage of (65%), followed by the field of ( educational programs) with the last rank at the rate of (62,33%) . Research recommended : 1-prparing supervisory publication that in traduce science teachers to some educational ideas and practices at the local and scientific level 2- frequent visits to science teachers by educational supervision in order to raise the efficiency and level of performance of the science teachers . To complete the study the researcher suggested : 1-conducting a similar study to evaluate science teachers according to the comprehensive quality standards in the other academic stages. 2- conducting more studies dealing with planning to develop an application (NCATE) in misan governorate . Keywords : Evaluating , the science teacher , according to the (NCATE) , educational supervisors .